Transcriptome Analysis of the Regulatory Mechanism of FoxO on Wing Dimorphism in the Brown Planthopper, Nilaparvata lugens (Hemiptera: Delphacidae) - Xu, Nan; Wei, Sheng-Fei; Xu, Hai-Jun (Insects (Basel, Switzerland), 2021)
The brown planthopper (BPH), Nilaparvata lugens, can develop into either short-winged (SW) or long-winged (LW) adults according to environmental conditions, and has long served as a model organism for exploring the mechanisms of wing polyphenism in insects. The transcription factor NlFoxO acts as a master regulator that directs the development of either SW or LW morphs, but the underlying molecular mechanism is largely unknown. Here, we microinjected SW-destined morphs with double stranded-RNA (dsRNA) targeting NlFoxO (dsNlFoxO) to change them into LW-winged morphs. In parallel, SW-destined morphs microinjected with dsRNA targeting the gene encoding green fluorescence protein (dsGfp) served as a negative control. The forewing and hindwing buds of 5th-instar nymphs collected at 24, 36, and 48 h after eclosion (hAE) were used for RNA sequencing. We obtained a minimum of 43.4 million clean reads from forewing and hindwing buds at a single developmental time. Differentially expressed genes (DEGs) were significantly enriched in various Gene Ontology (GO) terms, including cellular process, binding, and cell part. Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment pathway analysis showed that up-regulated genes in dsNlFoxO-treated forewing and hindwing buds were largely associated with the cell cycle and DNA replication. Furthermore, most up-regulated genes displayed higher expression at 24-, and 36-hAE relative to 48 hAE, indicating that wing cells in LW-destined wings might actively proliferate during the first 36 h in 5th-instar nymphs. Our findings indicated that LW development in BPH was likely dependent on the duration of cell proliferation in the 5th-instar stage, which sheds light on the molecular basis of wing polymorphism in insects.